Pengembangan Game Belajar Bangun Datar (LABADA) Kelas IV Sekolah Dasar - Selvia Ayu Wardani; Desy Dwi Riana; Dwi Kameluh Agustina (STIKes Ibnu Sina Ajibarang, 2023)
. Based on needs analysis and interviews, it shows that flat building material does not use innovative media and the minimal use of technology-based learning media, causes students to feel bored and less interested when learning in class. This research aims to produce LABADA Game products for feasible flat building materials. This type of RnD development research has been developed by Sugiono with seven steps, namely (1) looking for potential and problems at SDN Kepanjenlor 2, SDN Sentul 1 and SDN Sentul 3, (2) Carrying out research and collection by interviewing class IV teachers, distributing needs questionnaires students and observing mathematics learning, (3) product design is carried out by analyzing learning and planning product content, (4) Design validation is carried out by 9 validators consisting of 3 material validators each, media validator and language validator, (5) Design revision carried out based on expert advice, (6) Limited trials carried out by 10 class IV students and 5 class IV teachers, (7) product revisions based on teacher and student suggestions. The instrument in this research is a questionnaire. The feasibility results from material expert validators were 91.85%, media experts 89.44%, and language experts 86.67%. The results of the teacher's readability questionnaire for the LABADA game obtained a percentage of 91.29% and the results of the student's readability questionnaire obtained a percentage of 94.17%.